PENGARUH PERSEPSI KEBERMANFAATAN DAN PERSEPSI KEMUDAHAN TERHADAP PENGGUNAAN E-FILING DENGAN SOSIALISASI PERPAJAKAN SEBAGAI VARIABEL MODERASI PADA WAJIB PAJAK GURU DAN KARYAWAN TK-SD-SMP-SMK STRADA BUDI LUHUR - Skolastika Alva Adventia Indaryanti; Amelia Sandra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
The study was done to see if external and internal factors influenced the use of e-lizards in reporting as well.The Technology Acceptance Model (TAM) was a theory developed by Fred Davis in 1989 examined how the relationship between human perception as an internal factor and the use of information systems in everyday activities. Attribution Theory to explain between external factors and the use of e-components in reporting. Both theories are used n this research. The study carried out with private tax payers of Preschool-Elementary-Junior High-Vocational High School employees in Strada Budi Luhur. In this study the entire population will be used as a sample, due to a small population. The data analysis techniques used were validity and reliability tests, descriptive statistic tests, and classic assumption tests. Hypothetical verification using regression analysis tests, tests f, t, and coefficiencies. Based on research, it should be concluded that perceived usefulness have proven to have a positive effect on the use of e-Filing and tax socialization have strengthened the positive impact of perceived ease of use on e-Filing usage. On the other hand, perceived ease of use proved to have no positive effect on the use of e-Filing and tax socialization did not prove to strengthen the positive effects of a perceied usefulness on the use of e-taxation.